2008
DOI: 10.25011/cim.v31i3.3469
|View full text |Cite
|
Sign up to set email alerts
|

The significance of Toll-like receptor 4 (TLR4) expression in patients with chronic hepatitis B

Abstract: Results: TLR4 expressed mainly in the cytoplasm and some on cell membrane in hepatocytes. The staining scores of TLR4 expression in the liver tissues of patients with CHB were significantly higher than that of healthy controls. The liver tissues from patients with severe CHB expressed higher level of TLR4 than those from patients with mild CHB. Furthermore, the staining scores of TLR4 expression in the liver tissues of patients with CHB were positively correlated with the grading scores. Our results also showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…This increase is in agreement with the results of He et al [44] and Wei et al [45], who reported that TLR mRNA levels were increased significantly in chronic HCV and HBV patients.…”
Section: Discussionsupporting
confidence: 91%
“…This increase is in agreement with the results of He et al [44] and Wei et al [45], who reported that TLR mRNA levels were increased significantly in chronic HCV and HBV patients.…”
Section: Discussionsupporting
confidence: 91%
“…Its expression was found to be higher in the hepatocytes of patients with hepatitis B than in those of healthy controls. Moreover, the intensity of the immunohistochemical reaction positively correlated with grading scores (Wei et al 2008). We were able to demonstrate TLR4, TLR2, and TLR3 staining of hepatocytes in the livers of children with hepatitis C. The reaction was both cytoplasmic and cell membrane bound, but the former predominated (Mozer- Lisewska et al 2005).…”
Section: Incidence and Putative Function Of Prrs In Chronic Viral Hepmentioning
confidence: 68%
“…12,27 Opposing results have demonstrated that cell surface expression of TLR2 on PBMCs was significantly reduced in patients with CHB compared to healthy controls, and when stimulated with TLR2 and TLR4 agonists, PBMCs from patients with CHB exhibited decreased ability to produce cytokines (IL-6, IL-8, IL-12 and TNF-␣) compared with those from healthy controls. 9 Another group reported that PBMC expression of TLR2 was significantly reduced in HBeAg-positive patients compared to both controls and HBeAg-negative patients 10 and the same group demonstrated that the expression level of TLR2 was downregulated on PBMCs, hepatocytes and Kupffer cells from patients with HBeAg positive CHB as compared with HBeAg-negative CHB.…”
Section: Discussionmentioning
confidence: 79%